Effect of a dynamic loaded warm-up on vertical jump performance - Chattong, C.; Brown, L. E.; Coburn, J. W.; Noffal, G. (The Journal of Strength and Conditioning Research, 2010)
The vertical jump is a common movement performed in several sports. Considering the importance of this movement, an optimal warm-up protocol may help athletes perform at their maximum level. The purpose of this study was to investigate the potentiating effects of different levels of external resistance (weight vest) during box jumps on vertical jump performance. Twenty resistance trained males (22.45 yrs +/- 1.73,176.83 cm +/- 6.67, 76.98 kg +/- 8.56) participated in this study. Each subject's height, mass, and lateral femoral condyle height were measured on day one. Warm-up was performed by cycling for 5 minutes at a self selected pace. After the warm-up, subjects performed 5 jumps onto a box equivalent in height to their lateral femoral condyle. Following a 2 minute rest period, subjects performed 3 vertical jumps with the greatest height being recorded. On day one each subject performed a control condition with no external resistance to establish a baseline vertical jump height. On the following days they performed four random jump conditions with a weight vest equivalent to 5,10,15, or 20% of their bodyweight then rested for two minutes before performing 3 post-test vertical jumps. There was no significant interaction of condition by time for vertical jump height. However, there was a significant main effect for time (p < 0.05) with post-test scores (22.99 +/- 3.35 inches) being greater than pre-test scores (22.69 +/- 3.37 inches). Regardless of condition, post-test vertical jump performance was significantly greater than pre-test performance. Performing an active dynamic warm-up with or without a weight vest produced significantly greater post vertical jump performance. Findings from this study demonstrated that performing an active dynamic warm-up, with or without external resistance, can elicit a significant gain in vertical jump performance. This may allow athletes to perform at their maximum level in a performance environment. Future research should investigate the effects of different box heights, external loads, and volume on post vertical jump performance.